Farm size, food security, and welfare - Abay, Kibrewossen; Hirvonen, Kalle; Minten, Bart (International Food Policy Research Institute, 2020)
Chapter 6, “Farm Size, Food Security, and Welfare,” looks at the association of farm sizes with food security and welfare. This is an important issue in Ethiopian agriculture given that a growing rural population combined with limited scope for further land expansion and slow movement out of agriculture means that average (mean) farm sizes are decreasing in Ethiopia. Using cross-sectional data for the Ethiopian highlands, the authors find—surprisingly—small differences between owners of small and large farms in key welfare and food security outcomes. For example, a 20 percent increase in owned land area is associated with only a 0.7 percent increase in food consumption (measured in calories). Five adjustments are made by households residing on small farms to assure similar calorie intake as those residing on larger farms.12 First, they participate actively in land rental markets and, as a result, are able to double their cultivated land area on average. Second, they compensate their small landholdings with other income sources, mainly livestock and nonfarm businesses, permitting additional food purchases. Third, they cultivate their land more intensively, obtaining higher yields. Fourth, they favor more calorie-dense crops that are mostly used for their own consumption. Fifth, they produce as well as consume cheaper food items.